2021
DOI: 10.1016/j.euros.2021.05.003
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Study of the Relationship Between Clinical Outcomes After Enzalutamide and Serum Androgen Levels Measured via Liquid Chromatography-tandem Mass Spectrometry in Patients with Castration-resistant Prostate Cancer

Abstract: Background Enzalutamide (ENZ) is used to treat patients with castration-resistant prostate cancer (CRPC). However, the kinetics of serum androgens before and after ENZ treatment are unknown. Objective To elucidate the kinetics of serum androgens and explore the possibility of identifying a useful marker for predicting the effects of ENZ. Design, setting, and participants We conducted a prospective study from 2014 to 2018 at Gunma University H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…Lolli et al reported that changes in AR gene copy numbers and a T level < 0.09 nmol/L were associated with a poor prognosis, and a poor response to ENZ and abiraterone 18 . In our previous studies, higher blood androgen levels before ENZ treatment were associated with higher therapeutic efficacy and less frequent adverse events, such as anorexia, malaise, and fatigue 12 . Of the total population of 95 patients, 75 who had responded to treatment for at least 16 weeks were evaluated.…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…Lolli et al reported that changes in AR gene copy numbers and a T level < 0.09 nmol/L were associated with a poor prognosis, and a poor response to ENZ and abiraterone 18 . In our previous studies, higher blood androgen levels before ENZ treatment were associated with higher therapeutic efficacy and less frequent adverse events, such as anorexia, malaise, and fatigue 12 . Of the total population of 95 patients, 75 who had responded to treatment for at least 16 weeks were evaluated.…”
Section: Discussionmentioning
confidence: 61%
“…18 In our previous studies, higher blood androgen levels before ENZ treatment were associated with higher therapeutic efficacy and less frequent adverse events, such as anorexia, malaise, and fatigue. 12 Of the total population of 95 patients, 75 who had responded to treatment for at least 16 weeks were evaluated. The results showed that, in the High-T group, a good QoL score was maintained, although the difference from the Low-T group was not significant in the analysis including only patients who had responded well to treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[23][24][25] Our prospective study showed that blood androgen levels predicted drug efficacy. 21 Loli et al found that changing circulatory AR gene copy number and testosterone values <0.09 nmol/L were associated with poor outcomes and poor response to ENZ and abiraterone. 26 Recently, analyses of circulating tumor cells revealed that patients with amplified AR-related genes responded poorly to AR-targeting drugs such as abiraterone and ENZ.…”
Section: Discussionmentioning
confidence: 99%
“…We prospectively investigated 104 CRPC patients treated at the Department of Urology of Gunma University Hospital and affiliated hospitals between 2014 and 2018. 21 All patients received enzalutamide. We subjected samples collected during the prospective study to retrospective analysis using prognosis-related data obtained before and after treatment.…”
Section: Patients and Study Designmentioning
confidence: 99%